Preliminary examination of acceptability, feasibility, and effectiveness of internet-based cognitive behavioral therapy for treatment of depression and anxiety in infertile women - Farzan Kheirkhah; Mahbobeh Faramarzi; Shiva Shafierizi; Mohammad Chehrazi; Zahra Basirat (Heliyon, 2023)
Background: Despite a large body of evidence supporting the effectiveness of internet-based cognitive behavior therapy (ICBT) for the treatment of depression and anxiety, there is no report of the efficacy of ICBT program in the Iranian population. The present study aimed to test the acceptability, feasibility, and effectiveness of ICBT program for the treatment of depression or anxiety in infertile women. Method: This study consisted of two phases. In the first phase, we designed “Peaceful Mind”, an eight-session therapist-guided ICBT program. In the second phase, we tested the efficacy of the program by conducting 2-arm parallel group, non-inferiority randomized control trial, between October 2020 and July 2021.60 infertile women diagnosed with depression or anxiety disorders were divided randomly to ICBT treatment (n = 30) and face-to face CBT (n = 30). The participants received individual CBT sessions (60 min, over 8 weeks) and completed the questionnaires at the beginning, in mid-trial, and 8 weeks after the trial. The outcomes comprised Beck Depression Inventory (BDI-II), Beck Anxiety Inventory (BAI, Fertility problem inventory (FPI), Client Satisfaction Questionnaire (CSQ-8), and System usability scale (SUS). Results: The usability scores of the “Peaceful Mind” ICBT (M = 67.07, SD = 17.23, range = 1–100) and satisfaction with the treatment (M = 25.06, SD = 4.18, range = 1–32) were high. Patient adherence to the treatment in the ICBT group (86.6%) was the same as that in the CBT (73.3%). The between-group mean differences at the post-trial were −4.79 (CI 95% = −10.81 to 1.23) for depression scores and −4.15 (CI 95% = −9.52 to 1.22) for anxiety scores; both differences were within the non-inferiority margin points for the lower 95%CI. Conclusion: “Peaceful mind” ICBT was found to be feasible and accessible for delivering the treatment to the patients. The study confirmed that both ICBT face-to face CBT were equally effective in reducing depression and anxiety of the patients.